(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to introduce the concept of pseudo-UP ideals defined on a pseudo-UP algebra and by usingthis concept we study a uniform structure on a pseudo-UP algebra. Also, we study some properties of the topology whichis generated by a filter base on pseudo-UP algebra. Moreover, several results are obtained using the concept of pseudo-UPhomomorphisms